V shaped Tröger oligothiophenes boost triplet formation by ct mediation and symmetry breaking - Medina Rivero, Samara; Alonso-Navarro, Matías J.; Tonnelé, Claire; Marín-Beloqui, José Manuel; Suarez-Blas, Fátima; Clarke, Tracey M.; Kang, Seongsoo; Oh, Juwon; Ramos, M. Mar; Kim, Dong-Ho; Casanova, David; Segura, José L.; et al. (ACS, 2023)
A new family of molecules obtained by coupling Tröger's base unit with dicyanovinylene-terminated oligothiophenes of different lengths has been synthesized and characterized by steady-state stationary and transient time-resolved spectroscopies. Quantum chemical calculations allow us to interpret and recognize the properties of the stationary excited states as well as the time-dependent mechanisms of singlet-to-triplet coupling. The presence of the diazocine unit in Tröger's base derivatives is key to efficiently producing singlet-to-triplet intersystem crossing mediated by the role of the nitrogen atoms and of the almost orthogonal disposition of the two thiophene arms. Spin-orbit coupling-mediated interstate intersystem crossing (ISC) is activated by a symmetry-breaking process in the first singlet excited state with partial charge transfer character. This mechanism is a characteristic of these molecular triads since the independent dicyanovinylene-oligothiophene branches do not display appreciable ISC. These results show how Tröger's base coupling of organic chromophores can be used to improve the ISC efficiency and tune their photophysics.
Keywords: Química física; Bases (Química); Moléculas; Tröger Oligothiophenes; Interstate intersystem crossing; CT mediation; Symmetry breaking